Modeling and Specifying Requirements for Cyber-Physical Systems - Ordinez, Leonardo Damian (2013)
Cyber-physical systems have to do with a strong interaction between the physical world and a computing system, which should be transparent to an external observer. In this paper, an approach for modeling and specifying requirements for these systems is presented. It is called 3D Approach and it is based on the well known 4-Variable Model. The proposed extension intends to tackle the particularities involved in the development of cyberphysical systems by a multidisciplinary team and consequently it emphasizes a practical and applied point of view. The 3D Approach came out as the result of systematizing lessons learned in the design of a biodigester, which allows the anaerobic digestion of biomass for the production of biogas.